1992
DOI: 10.1093/cvr/26.10.950
|View full text |Cite
|
Sign up to set email alerts
|

Increase in functional activity rather than in amount of Gi-  in failing human heart with dilated cardiomyopathy

Abstract: These results suggest that in the failing human heart, there is an increase in functional activity rather than in amount of Gi, and an important part of functional expression of Gi-alpha may be regulated at the post-translational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Recent studies in mice and humans suggest that increases or dysregulation of G i signaling may underlie some human dilated cardiomyopathies 9,21,22 . Our control of Ro1 expression and activation will allow us to test both the short-and longterm biochemical, pathological, and gene expression effects induced by G i signaling in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in mice and humans suggest that increases or dysregulation of G i signaling may underlie some human dilated cardiomyopathies 9,21,22 . Our control of Ro1 expression and activation will allow us to test both the short-and longterm biochemical, pathological, and gene expression effects induced by G i signaling in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Feldman et al (1988) observed the increased activity of α G40 complex in the human failing heart and considered as a possible new marker for the severity of failing heart. Fu et al (1992) also concluded that the role of G i protein is crucial in the failing heart but it was observed an increase in functional activity rather than in its amount. In 1997 Ping et al (1997) during the pacing induced congestive heart failure (CHF) examined the alteration of β-ARs, AC activity and GRKs.…”
Section: Clinical Implications Of Alterations In β-Adrenoceptor Mechamentioning
confidence: 99%
“…Levels of G␣ i were increased in ventricles of patients with idiopathic DCM (4,8,27). Furthermore, decreased adenylyl cyclase activity (an effect of G i signaling) was found in hearts of patients with DCM (8,9,11). Despite the association between increased G i signaling and DCM, the mechanisms involved remain unclear.…”
mentioning
confidence: 99%